2016
DOI: 10.1002/eji.201646475
|View full text |Cite
|
Sign up to set email alerts
|

Targeted loss of SHP1 in murine thymocytes dampens TCR signaling late in selection

Abstract: SHP1 is a tyrosine phosphatase critical to proximal regulation of TCR signaling. Here, analysis of CD4-Cre SHP1fl/fl conditional knockout thymocytes using CD53, TCRβ, CD69, CD4 and CD8α expression demonstrates the importance of SHP1 in the survival of post selection (CD53+), single-positive thymocytes. Using Ca2+ flux to assess the intensity of TCR signaling demonstrated that SHP1 dampens the signal strength of these same mature, post-selection thymocytes. Consistent with its dampening effect, TCR signal stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 39 publications
8
43
0
Order By: Relevance
“…To test this possibility, we crossed mice carrying floxed alleles of Ptpn6 (Shp1) 19 with mice that express the Cre recombinase under the control of the distal promoter of Lck 17 . The distal Lck promoter drives Cre expression at late stages of T cell development, allowing TCR-dependent selection to occur under conditions of SHP-1 sufficiency 12,16,18,20 . We confirmed that SHP-1 was deleted in peripheral CD4+ (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this possibility, we crossed mice carrying floxed alleles of Ptpn6 (Shp1) 19 with mice that express the Cre recombinase under the control of the distal promoter of Lck 17 . The distal Lck promoter drives Cre expression at late stages of T cell development, allowing TCR-dependent selection to occur under conditions of SHP-1 sufficiency 12,16,18,20 . We confirmed that SHP-1 was deleted in peripheral CD4+ (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This was done using the motheaten ( me/me ) mouse model, in which all hematopoietic cells lack SHP-1 due to a splicing mutation 14 , as well as cell lines expressing dominant negative mutant forms of SHP-1 12 . However, one recent study 15 , using conditional T cell deletion of SHP-1 via CD4-Cre, challenged the role of SHP-1 in regulating T cell development, while another report using the same mouse model confirmed the role of SHP-1 during T cell development 16 . Here, we generated a conditional knockout mouse model wherein SHP-1 deletion is driven by the distal Lck promoter 17 , resulting in abrogation of SHP-1 expression in post-selection thymocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The phenotype of Ptpn6 −/− mice does not resemble that of Themis −/− mice as might have been predicted by Model 1 [24, 25]. In contrast to Themis −/− mice, positive selection is not markedly impaired in Ptpn6 −/− mice [24], although the survival of post-selection SP thymocytes is reduced, possibly due to enhanced negative selection [25].…”
Section: Examining the Evidence For Model 1 And Modelmentioning
confidence: 99%
“…In contrast to Themis −/− mice, positive selection is not markedly impaired in Ptpn6 −/− mice [24], although the survival of post-selection SP thymocytes is reduced, possibly due to enhanced negative selection [25]. In Themis −/− mice, a defect in thymocyte maturation is observed at the first stage of positive selection (TCR int CD69 int ) [1, 3] whereas Ptpn6 −/− mice do not exhibit a developmental defect until the later TCR hi CD69 hi post-selection stage [25]. Also, CD4 SP thymocyte and T cell numbers are unaffected or only slightly reduced in Ptpn6 −/− mice [24, 25] but are strongly diminished in Themis −/− mice [15].…”
Section: Examining the Evidence For Model 1 And Modelmentioning
confidence: 99%
See 1 more Smart Citation